Hadith #7395 - Sahih Muslim - Ishaq bin 'Abdullah bin Abi Farwa إسحاق بن عبد الله بن أبي فروة (Sahih Muslim)
‘I came across Tāwus and said: ‘So-and-so narrated to me such-and-such’. Then he said: ‘If your companion is trustworthy, then take from him.’
Grade: Sahih

Hadith #7448 - Sahih Muslim - Ishaq bin 'Abdullah bin Abi Farwa إسحاق بن عبد الله بن أبي فروة (Sahih Muslim)
‘What an excellent man is Baqiyyah, if it were not for the fact that he would provide a nickname for he was Abd ul-Quddūs ’.
Grade: Sahih